Management of neutropenic fever in a private hospital oncology unit. Issue 8 (6th August 2020) - Skiba, Rohen; Sikotra, Nisha; Ball, Timothy; Arellano, Astrid; Gabbay, Eli; Clay, Timothy D.
Abstract: Background: Neutropenic fever is a medical emergency, which poses a significant morbidity and mortality risk to cancer patients receiving chemotherapy. National guidelines recommend that patients presenting with suspected neutropenic fever receive appropriate intravenous antibiotics within 60 min of admission. Aim: We aimed to investigate the management of neutropenic fever in a large private oncology centre. Methods: A retrospective audit of all patients who presented to St John of God Hospital, Subiaco, in the 2017 calendar year, with a known solid organ malignancy and a recorded diagnosis of neutropenic fever was conducted. Patients were identified through the hospitals Patient Administration System and ICD‐10 codes. Information was collected from the hospital medical records using a standardised data collection tool. Results: There were 98 admissions relating to 88 patients with neutropenic fever during the study period. The median age was 64 years (range: 23–85 years) with 57 (65%) females. Antibiotic selections consistent with the Australian guidelines were made in 88 (89%) admissions. The mean time to antibiotic administration was 279 min, with a median of 135 min (range: 15–5160 min). Antibiotics were administered within the recommended time frame in only eight (11%) admissions. Conclusion: Clinicians prescribed antibiotics in accordance with national guidelines; however, there were systemic inefficiencies which resulted in delayed antibiotic initiation. This has resulted in implementation of strategies to minimise delay.